Avaliação do potencial evocado auditivo de longa latência (p300) na infecção pelo HIV em crianças e adolescentes - Andreza Batista Cheloni Vieira (2012)
Introduction: The HIV may cause, in pediatric population, an increase in the risk of Central Nervous System conditions related to alteration in cognition. In adults, such alterations may happen regardless the treatment with antiretroviral drugs; in infected children, this matter hasn't yet been assessed. Objective: Evaluate the cognitive processing of auditory information in children infected by the HIV and treated withHAART. Methods: A case-control study with 92 children from 8 through 9 years of age, 40 of whom being vertically infected by the HIV (study group) and 52 not infected, paired by gender and age. In the study group, patients assisted by Centro de Tratamento e Referência em Doenças Infecciosas e Parasitárias do Hospital das Clínicas da UFMG (Center of Treatment and Reference in Infectious and Parasitary Diseases of the Hospital das Clínicas of UFMG), in the control group, healthy children, not infected by the HIV, with good school performance, attending publiceducation (Instituto de Educação de Belo Horizonte). All participants were subjected to thorough clinical interviews, tonal threshold audiometric, imitanciometrics and long latency auditory evoking potential (P300). Medical records were reviewed regarding the antiretroviral scheme used, lymphocyte count CD4+ and viral load. The following were considered: 1) viral load: lower than 50, between 50 and 10,000 and higher than 10,000. copies; 2) CD4 + between 200-500 cells and higher than 500 cells. Results: All the participants included present normal tonal audiometric and imitanciometric evaluations. The P300 wave was observed in all tested children and the increase in latency was associated with a viral load superior to 10,000 copies (P=0.00). In the analysis divided in age groups, the association with a higher latency in P300 was observed in the group of children older than 10 with viral load higher than 10,000 copies (P= 0.06), the lymphocyte count CD4+ lower than 500 cells (P=0.02) and B classification of CDC (1994) (P=0.03). No class and/or retroviral scheme was associated to the alteration in the P300. Conclusions: The HIV infected children with an increase of viral load, CD4+ count lower than 500 cells or B classification of the CDC (1994) are entitled to having their cognitive abilities related to hearing being assessed. The inappropriate immunological control of HIV infection in pediatrics seems to have negative consequences for cognition, regardless of the regular treatment with antiretroviral drugs. A proper screening of the central auditory processing is indicated for HIV infected children with poor school performance. The results, if altered, encourage stimulation therapies, with satisfactory clinical response, especially when done still in childhood. The impact in public education could be obtained at low cost with the training of professional speech therapists of the public system with interdisciplinary intervention. In case of adults infected with the HIV, the objective evaluation of cognition through the P300 along with laboratory criteria may have relevant weight in the decision about the beginning of treatment.